Can the Sorghum Planting Industry in Less-Favoured Areas Promote the Income Increase of Farmers? An Empirical Study of Survey Data from 901 Samples in Luquan County - Renyi Yang; Zisheng Yang (Agriculture, 2022)
Poverty alleviation is the basic requirement of human social development. However, there is still a lack of quantitative research on the poverty alleviation effect of regional, characteristic industries. Few studies have focused on the increase of micro individual income and used more advanced policy evaluation tools for comparative analysis based on a quasi-experimental perspective. In addition, the existing research ignores the critical question: can characteristic industries really achieve sustainable development goals while bringing poverty alleviation results? We studied regional, characteristic industries from a new perspective, taking into account the poverty alleviation effect and regional sustainable development. Based on the survey data of 901 households of representative village committees of Tanglang and Dache in Luquan Yi and Miao Autonomous County, this study quantitatively analyzed the poverty alleviation effect of the sorghum planting industry by using the Propensity Score Matching Difference-in-Differences (PSM-DID) model. The adoption of the industrial alleviation policy has significantly increased the per capita net income of rural households in Tanglang and Dache village committees, by 2171.64 CNY and 1945.06 CNY, respectively. The estimation results of the whole sample show that the effect of the policy to the per capita net income of households is 1726.87 CNY. The development of the sorghum planting poverty alleviation industry in Luquan County has promoted income increase of households significantly, creating economic, social and ecological sustainability, and can provide a reference for less-favoured areas.